Plectasin: from evolution to truncation, expression, and better druggability - Li, Xuan; Hao, Ya; Yang, Na; Mao, Ruoyu; Teng, Da; Wang, Jianhua (Frontiers in Microbiology, 2023)
Non-computational classical evolution analysis of plectsain and its functional relatives can especially contribute tool value during access to meet requirements for their better druggability in clinical use. Staphylococcus aureus is a zoonotic pathogen that can infect the skin, blood, and other tissues of humans and animals. The impact of pathogens on humans is exacerbated by the crisis of drug resistance caused by the misuse of antibiotics. In this study, we analyzed the evolution of anti-Staphylococcus target functional sequences, designed a series of plectasin derivatives by truncation, and recombinantly expressed them in Pichia pastoris X-33, from which the best recombinant Ple-AB was selected for the druggability study. The amount of total protein reached 2.9 g/L following 120 h of high-density expression in a 5-L fermenter. Ple-AB was found to have good bactericidal activity against gram-positive bacteria, with minimum inhibitory concentration (MIC) values ranging between 2-16 μg/mL. It showed good stability and maintained its bactericidal activity during high temperatures, strong acid and alkali environments.Notably, Ple-AB exhibited better druggability, including excellent trypsin resistance, and still possessed approximately 50 % of its initial activity following exposure to simulated intestinal fluids for 1 h. In vitro safety testing of Ple-AB revealed low hemolytic activity against mouse erythrocytes and cytotoxicity against murine-derived macrophages. This study successfully realized the high expression of a new antimicrobial peptide (AMP), Ple-AB, in P. pastoris and the establishment of its oral administration as an additive form with low high trypsin resistance; the study also revealed its antibacterial properties, indicating that truncation design is a valuable tool for improving druggability and that the candidate Ple-AB may be a novel promising antimicrobial agent.